EU Law Chapter on EU State Aid Rules – The Bumpy Ride From ‘Subsidy Control’ to ‘Subsidy Governance’ - Szegedi, László; Teleki, Bálint (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The EU integration process has shaped EU State aid law and policy. This evolutionary process has also been reshaped by the EU’s expanding supranational competences, the ever-changing rules of procedure and methodology, and the different sets of actors involved in these policy cycles. This applies to the companies as beneficiaries of state aid, the Member States involved in providing such aid, and the EU actors, notably the Commission and the CJEU, in shaping state aid procedures and rules. The last decade has seen several challenges and opportunities for further development of this policy area. This chapter looks at the changes in the regulatory landscape in the light of the CJEU’s case-law on standing rights, the coronavirus and the energy market crisis, the EU Green Deal initiative and the tax avoidance cases before the CJEU. In addition, we may also see some future trends concerning the territorial distortions between Member States due to the highly different levels of state aid, or the compensation of these distortions by funds at EU level financed by a certain percentage of the aid approved and granted, and finally the use of the newly enacted Foreign Subsidies Regulation as an external tool to protect the Single Market.Keywords: state aid distortions, standing rights, coronavirus and energy market crisis, taxation avoidance cases, Foreign Subsidies Regulation